Keanekaragaman Iktiofauna Ekosistem Estuari Taman Hutan Raya Ngurah Rai, Bali - Gabrielle Aisya; Nyoman Dati Pertami; I Nyoman Giri Putra (Department of Marine Sciences, Faculty of Marine and Fisheries, Universitas Udayana, 2023)
The diversity of ichthyofauna is an important aspect that can be used to presume the aquatic environmental conditions. Therefore, this study aims to determine the diversity of ichthyofauna in Taman Hutan Raya (TAHURA) Ngurah Rai, Bali during the eastern season and transitional II season. The sample was collected from July 2022 – October 2022 using an experimental gill net. During the sampling period of this study, 413 fishes were caught, representing 18 different species from 17 genera, 14 families, and 12 orders. Based on the results of the analysis, the highest diversity value was found in the waters of Jimbaran, then the waters of Kampung Kepiting, while Serangan waters has the lowest diversity value (H’<1). The lowest uniformity index was found in the waters of Serangan because it is dominated by only one fish species, namely Ambassis macracanthus (Seriding Fish), while in the waters of Kampung Kepiting and Jimbaran, the uniformity is quite even. The highest dominance index was found in the waters of Serangan, while other water areas has no dominating species. The species composition found at all stations varied considerably, but the results of the IUCN status showed that most of the fishes were still in the category of data deficient and not evaluated. The highest abundance was found in the waters of Serangan. The water quality parameters of TAHURA Ngurah Rai showed that not all aspects are in accordance with quality standards for marine life.